Rehabilitasi Berbasis Masyarakat dalam Pemulihan Penyandang Disabilitas Mental di Kabupaten Cianjur Provinsi Jawa Barat - Rini Hartini Rinda; Roudhotul Jannah; Suheli Suheli; Tiara Tri Sofiani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Mental health is an important issue that cannot be ignored. The impact of poor quality of life, such as disability, neglect, inhumane treatment, not only on the sufferer, but also on the family, makes mental health issues need serious attention. Based on concern to make social rehabilitation for mental health disorders widely developed in Indonesian society, this study aim find out how community rehabilitation methods are used to recover people with mental disabilities in West Java. This study uses a qualitative approach with descriptive method. there are nine informants, including institutional administrators, people with mental disabilities who have recovered, and social service employees. Collecting data with in-depth interviews, observations, FGDs and study documentation. Qualitative data analysis with interactive techniques. The results of this study indicate that the methods used in social rehabilitation for people with mental disabilities are varied, namely using a medical approach in the form of drugs, and a religious and cultural approach, with reading the yellow book prayer, special rituals, and special treatment. The success of the recovery was recognized by each institution, as well as by the people with mental disabilities who recovered. The results also show that recovery does not mean returning to health, 100% normal, but recovering to be able to communicate with others, be independent and participate in family and community activities. The results also show that recovery varies, influenced by various factors. When viewed from the results of this study, the most important is the healing method used. The failure of recovery was also found, the cause was due to severe mental health conditions, inappropriate healing methods, and the lack of family support. Keywords: Mental Health, People with Disabilities, Social Rehabilitation, Community-Based Rehabilitation